Surfactant-assisted synthesis of anhydrous magnesium borates for Congo red photodegradation - Gul, Enis Muhammet; Dumanli, Fatma Tugce Senberber; Kipcak, Azmi Seyhun; Derun, Emek Moroydor (ELSEVIER SCI LTD, 2025)
Anhydrous magnesium borates were achieved by using a surfactant-assisted solid-state method at the different ratios of n-cetyl-n, n, n trimethylammonium bromide (CTAB) and sodium dodecyl sulfate (SDS). The samples were analyzed using X-ray diffraction (XRD), Fourier Transform infrared spectroscopy (FT-IR), BrunauerEmmett-Teller specific surface area analysis (BET), scanning electron microscopy and Energy Dispersive Spectroscopy (SEM-EDS) techniques. According to the characterization analyses, the optimum ratio for CTAB and SDS was determined. The XRD results identified the prepared powders as a mixture of Mg-3(BO3)(2), Mg2B2O5 and MgB4O7. The surfactant of SDS was found more beneficial for the enhanced characteristics of magnesium borates such as increasing surface area, homogeneity and decreasing particle sizes. The prepared samples were used in the Congo Red (CR) photodegradation. The photodegradation mechanism was explained by using radical trapping experiments. The photodegradation reaction was modelled by using the second-order Langmuir Hinshelwood kinetic method. The kinetic parameters could be summarized as a degradation percentage of 76 %, apparent coefficients (k(app)) between 0.0006 and 0.0037 min(-1), and a photocatalytic half-life (t(1/2)) of 31 min.
Keywords: Dye pollutant; Magnesium borate; Photodegradation; Synthesis; Surfactant; WHISKERS; Materials Science